1992
DOI: 10.1037/h0094344
|View full text |Cite
|
Sign up to set email alerts
|

Nightmare frequency and related sleep disturbance as indicators of a history of sexual abuse.

Abstract: The present study examined the relationship of sexual abuse to nightmare frequency and related sleep disturbance. Subjects were 539 undergraduate women, who completed a Nightmare/Sleep History Questionnaire, Beck Depression Inventory (BDI) and a questionnaire which inquired into histories of "unwanted sexual activity" and physical abuse. Based on their self report 124 women reported a history of some form of sexual abuse, 71 reported physical abuse and 344 no abuse. Analyses of covariance controlling for depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 15 publications
2
28
1
Order By: Relevance
“…For adults, strong long-term effects of traumatic experiences on sleep have been reported for combat veterans (Neylan et al, 1998) and Holocaust survivors (Kaminer and Lavie, 1991). Cuddy and Belicki (1992) studied a sample of undergraduate women and found higher nightmare and night terror frequencies, and greater difficulties returning to sleep after awakenings from nightmares for those students who reported a history of sexual or physical abuse. Also, Noll et al (2006) found in a longitudinal, prospective study that women sexually abused in childhood reported significantly greater rates of sleep disturbances in later adulthood than comparison participants.…”
Section: Discussionmentioning
confidence: 97%
“…For adults, strong long-term effects of traumatic experiences on sleep have been reported for combat veterans (Neylan et al, 1998) and Holocaust survivors (Kaminer and Lavie, 1991). Cuddy and Belicki (1992) studied a sample of undergraduate women and found higher nightmare and night terror frequencies, and greater difficulties returning to sleep after awakenings from nightmares for those students who reported a history of sexual or physical abuse. Also, Noll et al (2006) found in a longitudinal, prospective study that women sexually abused in childhood reported significantly greater rates of sleep disturbances in later adulthood than comparison participants.…”
Section: Discussionmentioning
confidence: 97%
“…First, disturbed sleep in adulthood may serve as an indicator for the assessment of abuse or trauma history and may also be a consequence of more serious underlying health problems. There is a pressing need for identification of symptoms that would suggest a history of abuse, specifically among women, so that proper treatment and care can be provided [53]. Diagnostic routines for sleep disorders typically fail to include an assessment of trauma history unless the patient is suspected of having depression or PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic routines for sleep disorders typically fail to include an assessment of trauma history unless the patient is suspected of having depression or PTSD. However, mounting evidence suggests that ACEs and sleep disorders are associated regardless of mental health status [21, 23, 42, 52, 53]. …”
Section: Discussionmentioning
confidence: 99%
“…Nightmares result from exposure to all types of traumatic events (Cuddy & Belicki, 1992;DeMol, 1998;Lansky, 1995;Neylan et al, 1998) and both nightmares and sleep disturbances can continue for decades following a traumatic experience (Kuch & Cox, 1992;Lavie, Hefez, Halperin, & Enoch, 1979;Rosen, Reynolds, Yeager, Houck, & Hurwitz, 1991;Schreuder, Egmond, Kleijn, & Visser, 1998;van der Kolk, Blitz, Burr, Sherry, & Hartmann, 1984). Nightmares often have been viewed as uncontrollable processes that are engendered by the unconscious mind as a manifestation of an unresolved conflict related to a previous traumatic experience (Hartmann, 1984;Lansky, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Trauma nightmares among chronic PTSD patients often occur during non-REM sleep and earlier in the sleep cycle (Glaubman, Mikulincer, Porat, Wasserman, & Birger, 1990;Kramer & Kinney, 1988;van der Kolk et al, 1984). Furthermore, nontraumatic nightmares rarely replicate a historical event in factual sequence (Arvanitakis, Jodoin, Lester, Lussier, & Robertson, 1993;Cuddy & Belicki, 1992;Pagel, Vann, & Altomare, 1995;Terr, 1983;Wood & Bootzin, 1992), while combat and rape-related nightmares are often an historical re-experience of the actual event (Hartmann, 1996).…”
Section: Introductionmentioning
confidence: 99%